Дослідження впливу технологічного середовища на роботу гомогенізаторів - Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianska, Natalia; Болтянський, Олег Володимирович; Болтянский, Олег Владимирович; Boltianskyi, Oleh; Орел, Олександр Миколайович; Орел, Александр Николаевич; Orel, Oleksandr; Непарко, Т. А. (My University, 2021)
UK: У статті зазначено, що в більшості випадків довговічність обладнання переробних і харчових виробництв пов’язана з проблемою спрацювання окремих деталей та вузлів. Тому підвищення зносостійкості деталей вузлів тертя є основним напрямком підвищення надійності і довговічності обладнання. У загальній проблемі надійності, точності і довговічності машин, механізмів і приладів основне місце належить питанням тертя, зношуванню поверхонь деталей і робочих органів, які є між собою в дуже складних кореляційних залежностях. Встановлено, що знос обладнання харчової промисловості, підкоряючись в більшості випадків загальним закономірностям, встановленим для контакту твердих тіл, має свою специфіку, яка полягає в тому, що робочі органи зношуються не внаслідок контакту з іншими деталями, а в результаті взаємодії з продуктами переробки. Визначено, що гомогенізатори молочних продуктів працюють в умовах середнього і сильного ступеня агресивного впливу технологічного середовища. Дослідження показують низьку експлуатаційну надійність клапанного механізму і плунжерів високого тиску гомогенізаторів. EN: The article indicates that in most cases the durability of equipment for processing and food industries is associated with the problem of wear of individual parts and assemblies. Therefore, increasing the wear resistance of parts of friction units is the main direction of increasing the reliability and durability of equipment. In the general problem of reliability, accuracy and durability of machines, mechanisms and devices, the main place belongs to the issues of friction, wear of the surfaces of parts and working bodies, which are among themselves in very complex correlations. It has been established that the wear of food industry equipment, obeying in most cases the general laws established for the contact of solids, has its own specificity, which consists in the fact that the working bodies wear out not due to contact with other parts, but as a result of interaction with processed products. It has been determined that homogenizers of dairy products operate under conditions of medium and strong aggressive action of the technological environment. Research shows low operational reliability of the valve train and high pressure plungers of homogenizers. Suction and discharge valves are the same and have a complex shape with surfaces. Each of these surfaces has its own wear characteristics. The guide wears out from the material that moves along it, so shells form on the surface.The cavities created in the grooves of the guides are oriented along the direction of movement of the product and can be attributed to chemical-mechanical wear, which corresponds to oxidative wear that occurs at high pressure and the presence of surfactants. The greatest wear of the plunger surface in diameter is at the extreme points of the working stroke, that is, where the plunger stops and changes the direction of movement. It should also be noted that the plungers operate with a guaranteed clearance with the plunger block and contact only with the seal, the hardness of which is significantly lower than the plunger material. In this case, the appearance of the nature of the wear of the plunger surface during macroanalysis has a pronounced abrasive nature. RU: В статье указано, что в большинстве случаев долговечность оборудования перерабатывающих и пищевых производств связана с проблемой износа отдельных деталей и узлов. Поэтому повышение износостойкости деталей узлов трения является основным направлением повышения надежности и долговечности оборудования. В общей проблеме надежности, точности и долговечности машин, механизмов и приборов основное место принадлежит вопросам трения, износу поверхностей деталей и рабочих органов, которые находятся между собой в очень сложных корреляционных зависимостях. Установлено, что износ оборудования пищевой промышленности, подчиняясь в большинстве случаев общим закономерностям, установленным для контакта твердых тел, имеет свою специфику, которая заключается в том, что рабочие органы изнашиваются не вследствие контакта с другими деталями, а в результате взаимодействия с продуктами переработки. Определено, что гомогенизаторы молочных продуктов работают в условиях средней и сильной степени агрессивного воздействия технологической среды. Исследования показывают низкую эксплуатационную надежность клапанного механизма и плунжеров высокого давления гомогенизаторов.
Research of the influence of the technological environment on the work of homogenizers
Исследование влияния технологического среды на работу гомогенизаторов
Keywords: молочна промисловість; механічна обробка молока; гомогенізатор; знос; технологічне середовище; dairy industry; mechanical milk processing; homogenizer; wear; process medium; молочная промышленность; механическая обработка молока; гомогенизатор; износ; технологическая среда